Impact of single nucleotide polymorphisms of immunomodulatory factors on treatment response and prognosis in acute myeloid leukemia - Li, Mingying; Sun, Tao; Chang, Mengyuan; Liu, Tingting; Feng, Lei; Zhang, Di; Wu, Yuyan; Ma, Yuechan; Ma, Huixian; Meng, Guangqiang; Ji, Chunyan; Ye, Jingjing (Frontiers in Immunology, 2025)
BackgroundAcute myeloid leukemia (AML) is a hematologic malignancy characterized by poor overall survival (OS). The impaired function, altered phenotype, and abnormal distribution of T cells create an immunosuppressive microenvironment in AML, affecting the efficacy of chemotherapy. Studies have shown that differentiated monocyte-like AML cells can express various immunomodulatory factors, resulting in T cell phenotypic changes and the development of an immunosuppressive AML microenvironment.MethodsSeven single nucleotide polymorphisms (SNPs) of four immunomodulatory factors—HMOX1, TXNIP, TNSF10/TRAIL, and TNFAIP2—were selected and analyzed in 255 non-M3 AML patients and 316 healthy controls. SNP genotyping was conducted using the MassARRAY platform. Furthermore, we analyzed the relationship between AML susceptibility, bone marrow (BM) blast percentage, clinical characteristics, treatment response, and prognosis with the selected SNPs.ResultsThe study indicated that HMOX1 rs2071746 and TNFAIP2 rs1132339 are associated with BM blasts at the diagnosis of AML patients. TXNIP rs7211 is associated with sensitivity to cytarabine- and anthracycline-induced chemotherapy in AML, while TXNIP rs9245 is associated with AML relapse. Moreover, TRAIL/TNFSF10 rs12488654 is associated with the overall survival of AML patients, and the AA genotype of TRAIL/TNFSF10 rs12488654 may be an independent favorable factor for AML prognosis.ConclusionsOur results on the association between AML and SNPs in HMOX1, TXNIP, TNSF10/TRAIL, and TNFAIP2 genes provide an important reference for predicting the treatment response and prognosis of AML patients.